RESEARCH WORK AS THE FOUNDATION FOR TRAINING FUTURE SPECIALISTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article analyzes the role of research activities in the preparation of future researchers and the ability of a specialist to research activities. Research activity, being one of the most important areas of functioning of a modern medical university, creates the basis for effective innovation and requires great attention in the training of future medical researchers.